Ecological Origins of Object Salience: Reward, Uncertainty, Aversiveness, and Novelty - Ghazizadeh, Ali; Griggs, Whitney; Hikosaka, Okihide (Frontiers in Neuroscience, 2016)
Among many objects around us, some of them are more salient than others (i.e., attract our attention automatically). Some objects may be inherently salient (e.g., brighter), but others may become salient by virtue of their ecological relevance through experience. However, the importance of ecological experience in guiding attention has not been studied systematically. To address this question, we let subjects (macaque monkeys) view a large number of complex objects (>300), each experienced repeatedly (>5 days) with rewarding, aversive or no outcome association (mere-perceptual exposure). Test of salience was done on separate days using free viewing with no outcome. We found that gaze was biased among the objects from the outset, affecting saccades to objects or fixations within objects. When the outcome was rewarding, gaze preference was stronger (i.e. positive) for objects with larger or equal but uncertain rewards. The effects of aversive outcomes were variable. Gaze preference was positive for some outcome associations (e.g. airpuff), but negative for others (e.g. time-out), possibly due to differences in threat levels. Finally, novel objects attracted gaze, but mere perceptual exposure of objects reduced their salience (learned negative salience). Our results show that, in primates, object salience is strongly influenced by previous ecological experience and is supported by a large memory capacity. Owing to such learned salience, the capacity to rapidly choose important objects can grow during the entire life to promote biological fitness.